2017
DOI: 10.1002/anie.201706921
|View full text |Cite
|
Sign up to set email alerts
|

Potential‐Cycling Synthesis of Single Platinum Atoms for Efficient Hydrogen Evolution in Neutral Media

Abstract: Single‐atom catalysts (SACs) have exhibited high activities for the hydrogen evolution reaction (HER) electrocatalysis in acidic or alkaline media, when they are used with binders on cathodes. However, to date, no SACs have been reported for the HER electrocatalysis in neutral media. We demonstrate a potential‐cycling method to synthesize a catalyst comprising single Pt atoms on CoP‐based nanotube arrays supported by a Ni foam, termed PtSA‐NT‐NF. This binder‐free catalyst is centimeter‐scale and scalable. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
282
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 468 publications
(289 citation statements)
references
References 54 publications
5
282
1
1
Order By: Relevance
“…[20] Metal-free catalysts,s uch as boron carbide, [23] porous carbon, [24] and their derivatives, [25,26] are alternative materials,o fw hich boron carbide (B 4 C) nanosheets presented the highest FE of 15.95 %a nd ac orresponding NH 3 yield rate of 26.57 mgh À1 mg À1 cat . [28][29][30][31] Considering that nearly all natural N 2 is fixed with the enzyme nitrogenase produced in bacteria, and the active center of the nitrogenase is aM o-based structure, [32] single Mo atoms could be ap romising catalyst. Thea ctivity of metal-based nanocatalysts is highly influenced by their size.…”
mentioning
confidence: 99%
“…[20] Metal-free catalysts,s uch as boron carbide, [23] porous carbon, [24] and their derivatives, [25,26] are alternative materials,o fw hich boron carbide (B 4 C) nanosheets presented the highest FE of 15.95 %a nd ac orresponding NH 3 yield rate of 26.57 mgh À1 mg À1 cat . [28][29][30][31] Considering that nearly all natural N 2 is fixed with the enzyme nitrogenase produced in bacteria, and the active center of the nitrogenase is aM o-based structure, [32] single Mo atoms could be ap romising catalyst. Thea ctivity of metal-based nanocatalysts is highly influenced by their size.…”
mentioning
confidence: 99%
“…Therefore,g reat efforts have been devoted to increase the platinum utilization as well as to improve the HER activity of Pt-based catalysts. [14,15] ForSACs, the coordination environments of metal atoms will greatly influence their electronic structures,a nd subsequently affect their catalytic activity. [9][10][11][12][13] More recently,P tS ACsw ith individual Pt atoms anchored on the supports of carbon nanotube and CoP have also been developed as efficient HER electrocatalysts.…”
mentioning
confidence: 99%
“…For the water‐splitting cell, the anode was a thin layer of Zn x Co 3‐x O 4 , whereas the cathode was a CoP‐based nanotube array decorated with single Pt atoms . The synthetic methods of preparing the anode and the cathode can be found in studies previously reported by our group ,. The apparent generation of H 2 and O 2 bubbles is observed on the two electrodes (Movie S1), which provides the initial assessment into the feasibility of a ZAB using an NH 3 ‐treated NP‐CT‐1000 as the air electrode in an operational water electrolysis system.…”
Section: Resultsmentioning
confidence: 90%
“…To further demonstrate the potential applications of our assembled ZAB in electrocatalysis, two ZABs connected in series were integrated with a water‐splitting cell (Figure c). For the water‐splitting cell, the anode was a thin layer of Zn x Co 3‐x O 4 , whereas the cathode was a CoP‐based nanotube array decorated with single Pt atoms . The synthetic methods of preparing the anode and the cathode can be found in studies previously reported by our group ,.…”
Section: Resultsmentioning
confidence: 99%